Opening a donor's wallet: The influence of appeal scales on likelihood and magnitude of donation - De Bruyn, Arnaud; Prokopec, Sonja (Journal of Consumer Psychology, 2013)
AbstractWe examine the influence of appeal scales on the likelihood and magnitude of donation in a large field experiment. We argue and show that the leftmost anchor on the appeal scale most strongly influences the likelihood of donating; the lower the anchor, the higher the donation likelihood. Furthermore, our findings indicate that increasing the steepness of the amounts on the appeal scale increases the magnitude of donations. Both effects are stronger for infrequent than for frequent donors. Our results demonstrate that by using what a charity knows about past donor behavior, it can alter appeal scales to change donation behavior.